2006
DOI: 10.1155/2006/610489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Information Level and Coping Style on Pain and Anxiety in Needle Liver Biopsy

Abstract: Biopsy of the liver is an important diagnostic procedure. The procedure is invasive and may be painful for patients. Sedative drugs are not used because the associated drop in blood pressure mimics hemorrhage, a major complication of the procedure. Cognitive and behavioural techniques have been used to decrease stress in patients undergoing other medical procedures. In the present study, it is postulated that providing procedural and sensory information may reduce patient anxiety levels. Patient coping styles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Potential mechanisms to account for these associations include impaired inflammatory response to injury in chronic (Kiecolt-Glaser et al, 1995) or acute stress (Marucha et al, 1998), aversive conditioning related to stress (Robinson et al, 2013), neuro-endocrine alterations (Catania et al, 2009) and shared genetic susceptibility (Zhou et al, 2008). It remains to be prospectively determined if technical factors designed to reduce complications (Hilzenrat et al, 2006; Patout et al, 2015) will impact state anxiety and individuals’ LP experience. Future studies aimed at improving pre-LP perception to enhance the experience of patients and study participants should examine other factors which impact anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms to account for these associations include impaired inflammatory response to injury in chronic (Kiecolt-Glaser et al, 1995) or acute stress (Marucha et al, 1998), aversive conditioning related to stress (Robinson et al, 2013), neuro-endocrine alterations (Catania et al, 2009) and shared genetic susceptibility (Zhou et al, 2008). It remains to be prospectively determined if technical factors designed to reduce complications (Hilzenrat et al, 2006; Patout et al, 2015) will impact state anxiety and individuals’ LP experience. Future studies aimed at improving pre-LP perception to enhance the experience of patients and study participants should examine other factors which impact anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The fear-avoidance model of Vlayen and Linton [ 41 ] would provide a good vehicle by which to empirically test such questions. Finally, sample size and power calculations for our study were based on similar studies in this area [ 42 ]. Effect sizes observed were mainly medium which suggests that the present sample size, whilst adequate, could have been increased slightly.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, monitors and blunters are affected differently by information. Although the findings are not conclusive [ 23 ], it appears that individuals who prefer to have information and are given information tend to become less anxious, while those who have a low preference for information but are given information tend to become more anxious [ 13 , 24 - 29 ]. For example, Morgan et al [ 30 ] found that, before a colonoscopy, patients given information congruent with their coping style experienced significantly less self-reported anxiety after the information intervention and spent less time in recovery.…”
Section: Introductionmentioning
confidence: 99%